Short‐term modern life‐like stress exacerbates Aβ‐pathology and synapse loss in 3xTg‐AD mice. (14th July 2015) - Baglietto‐Vargas, David; Chen, Yuncai; Suh, Dongjin; Ager, Rahasson R.; Rodriguez‐Ortiz, Carlos J.; Medeiros, Rodrigo; Myczek, Kristoffer; Green, Kim N.; Baram, Tallie Z.; LaFerla, Frank M.
Abstract Alzheimer's disease (AD) is a progressive neurological disorder that impairs memory and other cognitive functions in the elderly. The social and financial impacts of AD are overwhelming and are escalating exponentially as a result of population aging. Therefore, identifying AD‐related risk factors and the development of more efficacious therapeutic approaches are critical to cure this neurological disorder. Current epidemiological evidence indicates that life experiences, including chronic stress, are a risk for AD. However, it is unknown if short‐term stress, lasting for hours, influences the onset or progression of AD. Here, we determined the effect of short‐term, multi‐modal 'modern life‐like' stress on AD pathogenesis and synaptic plasticity in mice bearing three AD mutations (the 3xTg‐AD mouse model). We found that combined emotional and physical stress lasting 5 h severely impaired memory in wild‐type mice and tended to impact it in already low‐performing 3xTg‐AD mice. This stress reduced the number of synapse‐bearing dendritic spines in 3xTg‐AD mice and increased Aβ levels by augmenting AβPP processing. Thus, short‐term stress simulating modern‐life conditions may exacerbate cognitive deficits in preclinical AD by accelerating amyloid pathology and reducing synapse numbers. <boxed-text content-type="graphic" id="jnc13195-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Epidemiological evidence indicates that life experiences, including chronic stress, are a risk for Alzheimer disease (AD). However, it is unknown if short stress in the range of hours influences the onset or progression of AD. Here, we determined the effect of short, multi‐modal 'modern‐lifelike'stress on AD pathogenesis and synaptic plasticity in mice bearing three AD mutations (the 3xTg‐AD mouse model). We found that combined emotional and physical stress lasting 5 h severely impaired memory in wild‐type mice and tended to impact it in already low‐performing 3xTg‐AD mice. This stress reduced the number of synapse‐bearing dendritic spines in 3xTg‐AD mice and increased Aβ levels by augmenting AβPP processing. Thus, short stress simulating modern‐life conditions may exacerbate cognitive deficits in preclinical AD by accelerating amyloid pathology and reducing synapse numbers.